Multi-factor Quality Assessment of the Nursing Care for the Elderly Patients - V. Viryasov , Andrey (International Journal of Psychosocial Rehabilitation, 2020)
The role of analysis of the performance quality of nursing care in hospitals and inpatient facilities in the provision of medical care to elderly citizens is quite increasing, given the modern conditions of health care development with the growth of the volume of patients of elderly and senile age, as well as the overall significance of nursing personnel with the expansion of treatment methods. The presented study aimed to develop a method of generalized assessment of the performance quality of the nursing personnel in the provision of medical care to elderly patients. Statistical processing of the results of the study included the use of the following methods: calculation of the average absolute and relative values with the calculation of the average error on the statistical aggregate of 112 nurses surveyed. The study developed a method of generalized assessment of the performance quality of nurses and included four criteria: 1. Assessment of the quality of medical prescriptions. 2. Assessment of quality of supervision of elderly patients with age-associated concomitant diseases. 3. Care quality assessment. 4. Readiness to provide emergency care to elderly patients. As a part of the comparative analysis of the quality criteria of nursing, the highest score was obtained by the criterion of commitment to provide emergency care to elderly patients with age-associated concomitant diseases; the latter fact may indicate the readiness of nurses to provide care to such patients in the inpatient facilities.